Technological Change - Coron, Clotilde (Innovation, entrepreneurship, management series. Technological changes and human resources set, 2020)
Technological change is exciting as much as it is daunting. The arrival of new digital tools affects consumption patterns, types of employment and working conditions, and can pose challenges to organizations and individuals alike. Indeed, although technological change is a factor for economic growth, it can also be an amplifier, or even a catalyst, of inequality. It is also a social change and interacts in complex ways: technology is both the source and the consequence of social transformation. To understand technological change and to harness its effects, this book studies transformations at different levels (societal, organizational and individual). In its analysis of the subject, it also draws on a number of disciplines of the human and social sciences, such as anthropology, sociology and psychology.